First-order valence transition: Neutron diffraction, inelastic neutron scattering, and x-ray absorption investigations on the double perovskite Ba2PrRu0.9Ir0.1O6 - Sannigrahi, J; Adroja, D; Ritter, C; Kockelmann, W; Hillier, A; Knight, K; Boothroyd, A; Wakeshima, M; Hinatsu, Y; Mosselmans, J; Ramos, S (American Physical Society, 2019)
Bulk studies have revealed a first-order valence phase transition in Ba2PrRu1−xIrxO6 (0.10 ≤ x ≤ 0.25), which is absent in the parent compounds with x = 0 (Pr3+) and x = 1 (Pr4+), which exhibit antiferromagnetic order with transition temperatures TN = 120 and 72 K, respectively. In the present study, we have used magnetization, heat capacity, neutron diffraction, inelastic neutron scattering and x-ray absorption measurements to investigate the nature of the Pr ion in x = 0.1. The magnetic susceptibility and heat capacity of x = 0.1 show a clear sign of the first order valence phase transition below 175 K, where the Pr valence changes from 3+ to 4+. Neutron diffraction analysis reveals that x = 0.1 crystallizes in a monoclinic structure with space group P21/n at 300 K, but below 175 K two phases coexist, the monoclinic having the Pr ion in a 3+ valence state and a cubic one (Fm3m) having the Pr ion in a 4+ valence state. Clear evidence of an antiferromagnetic ordering of the Pr and Ru moments is found in the monoclinic phase of the x = 0.1 compound below 110 K in the neutron diffraction measurements. Meanwhile the cubic phase remains paramagnetic down to 2 K, a temperature below which heat capacity and susceptibility measurements reveal a ferromagnetic ordering. High energy inelastic neutron scattering data reveal well-defined highenergy magnetic excitations near 264 meV at temperatures below the valence transition. Low energy INS data show a broad magnetic excitation centred at 50 meV above the valence transition, but four well-defined magnetic excitations at 7 K. The high energy excitations are assigned to the Pr4+ ions in the cubic phase and the low energy excitations to the Pr3+ ions in the monoclinic phase. Further direct evidence of the Pr valence transition has been obtained from the x-ray absorption spectroscopy. The results on the x = 0.1 compound are compared with those for x = 0 and 1.